Tinjauan Hukum Terhadap Pemberian Pelayanan Kesehatan Dan Makanan Terhadap Narapidana ( Studi Kasus Di Lembaga Pemasyarakatan Tanjung Gusta Medan ) - Aliftha Rozakiya; Agus Salim Daulay; Wessy Trisna (JUNCTO: Jurnal Ilmiah Hukum, 2019)
In the Law of the Republic of Indonesia Number 12 Year 1995 regarding Penitentiary states that one of the rights of prisoners is to get adequate health and food services, health services and foods that meet health requirements. This research is a kind of juridical-empirical research with the fact approach and the statue approach. Data collection procedures used are interviews, documentation and observation. Data analysis uses descriptive qualitative analysis methods. The results of research that have been carried out that fulfillment of the rights of TanjungGustaLapas inmates in getting health and food services has been going well according to applicable laws and regulations. However, due to over capacity, health and food services are less than optimal. General obstacles faced by TanjungGustaLapas Medan officers are inmates who are not yet registered as BPJS holders, over capacity which causes health and food services as well as skills training for inmates less than optimal.